Cost items in melanoma patients by clinical characteristics and time from diagnosis - Buja, Alessandra; Cozzolino, Claudia; Zanovello, Anna; Geppini, Ruggero; Miatton, Andrea; Zorzi, Manuel; Manfredi, Mariagiovanna; Bovo, Emanuela; Del Fiore, Paolo; Tropea, Saveria; dall’Olmo, Luigi; Rossi, Carlo Riccardo; et al. (Frontiers in Oncology, 2023)
Costs related to the care of melanoma patients have been rising over the past few years due to increased disease incidence as well as the introduction of innovative treatments. The aim of this study is to analyse CMM cost items based on stage at diagnosis, together with other diagnostic and prognostic characteristics of the melanoma. Analyses were performed on 2,647 incident cases of invasive CMM that were registered in 2015 and 2017 in the Veneto Cancer Registry (RTV). Direct melanoma-related costs per patient were calculated for each year ranging from 2 years before diagnosis to 4 years after, and were stratified by cost items such as outpatient services, inpatient drug prescriptions, hospital admissions, hospice admissions, and emergency room treatment. Average yearly costs per patient were compared according to available clinical-pathological characteristics. Lastly, log-linear multivariable analysis was performed to investigate potential cost drivers among these clinical-pathological characteristics. Overall, the average direct costs related to melanoma are highest in the first year after diagnosis (€2,903) and then decrease over time. Hospitalization costs are 8 to 16 times higher in the first year than in subsequent years, while the costs of outpatient services and inpatient drugs decrease gradually over time. When stratified by stage it is observed that the higher expenditure associated with more advanced stages of CMM is mainly due to inpatient drug use. The results of the present study show that grouping patients according to tumour characteristics can improve our understanding of the different cost items associated with cutaneous malignant melanoma. CMM patients experience higher costs in the first year after diagnosis due to higher hospitalization and outpatient services. Policy makers should consider overall and stage-specific annual costs when allocating resources for the management of CMM patients.